Iron L3-edge energy shifts for the full range of possible 3d occupations within the same oxidation state of iron halides. Issue 33 (12th August 2022) - Flach, Max; Hirsch, Konstantin; Timm, Martin; Ablyasova, Olesya S.; da Silva Santos, Mayara; Kubin, Markus; Bülow, Christine; Gitzinger, Tim; von Issendorff, Bernd; Lau, J. Tobias; Zamudio-Bayer, Vicente
Abstract : Chemical shift spread of 420meV of formally identical metal centers solely induced by change in metal 3d occupation. Abstract : Oxidation states are integer in number but d n configurations of transition metal centers vary continuously in polar bonds. We quantify the shifts of the iron L3 excitation energy, within the same formal oxidation state, in a systematic L-edge X-ray absorption spectroscopy study of diatomic gas-phase iron(ii ) halide cations, [FeX] +, where X = F, Cl, Br, I. These shifts correlate with the electronegativity of the halogen, and are attributed exclusively to a fractional increase in population of 3d-derived orbitals along the series as supported by charge transfer multiplet simulations and density functional theory calculations. We extract an excitation energy shift of 420 meV ± 60 meV spanning the full range of possible 3d occupations between the most ionic bond in [FeF] + and covalently bonded [FeI] + .